The influence illegal fishing surveillance policies on marine fisheries business - Umam, Saiful; Ma'arif, Syamsul; Zulbainarni, Nimmi (Indonesian Journal of Multidisciplinary Science, 2023)
Illegal fishing that occurs in Indonesian waters has the potential to harm the marine fisheries business. The government seeks to overcome losses due to illegal fishing through  policies and surveillance programs through increasing the fleet of surveillance vessels, increasing operations by sea and air and utilizing information technology. Surveillance  of illegal fishing is a public policy, in  order to measure the impact and benefits of the policy, economic valuation is needed as a basis for stating that the policy is feasible and provides benefits presented in a value. This study aims to analyze the direct and indirect impact of illegal fishing Surveillance policies on the marine fisheries business. The research method uses producer surplus and analysis uses Extended Cost Benefit Analysis (ECBA). The results showed that  the policy of increasing Surveillance provides  positive benefits of Rp.1.8 trillion/year, so the policy is feasible. The policy has the potential to save economic and social losses, when the supervision conditions before the policy of increasing Surveillance of social and economic impacts obtained amounted to Rp.466.9 billion / year and after the policy increased Surveillance to Rp. 2.3 trillion / year. The policy of increasing supervision greatly affects the fisheries business at sea, namely the needs and supply of fish for raw materials for the fishery industry are met, increasing the productivity of catches, absorption of labor as fishermen on ships, sufficient fuel stocks and for the government, state revenues from PNBP and fisheries taxes increase.